The impact of insufficient implementation of Local Government Authorities’ (LGAs) budgetary plans - Masanja, Sabuni (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for award of the Degree of Master of Science in Accounting and Finance (MSc A&F) of Mzumbe University